Meanings of Rough Sex across Gender, Sexual Identity, and Political Ideology: A Conditional Covariance Approach. Issue 6 (18th August 2022) - Svetina Valdivia, Dubravka; Herbenick, Debby; Fu, Tsung-chieh; Eastman-Mueller, Heather; Guerra-Reyes, Lucia; Rosenberg, Molly
Abstract: The purpose of this study was to investigate how various subgroups based on gender, sexual identity, and political ideology conceptualize rough sex. We used available data from a 2020 survey of randomly sampled undergraduate students at a large public university in the Midwestern U.S. ( n =  4, 989). The dichotomous responses to 13 items on the rough sex meaning scale were analyzed using a conditional covariance approach to better understand which behaviors commonly described as rough sex behaviors were prevalent. Our results showed that rough sex was conceptualized largely as a two-dimensional construct for vast majority of subgroups. Across all subgroups, nine of the 13 behaviors clustered along two dimensions in the same way. Specifically, four behaviors related to hair pulling, being pinned down, hard thrusting, and throwing someone onto a bed clustered together as one dimension (spanking and tearing clothes off being present along this dimension for vast majority of the subgroups). Being tied up, slapping, choking, punching, and making someone have sex behaviors formed a separate dimension of rough sex across all studied groups (with biting and scratching being associated with this dimension for vast majority of subgroups).